Using blockchain technology for ensuring students results traceability for instrumentation classes. (December 2021) - Zet, Cristian; Dumitriu, Gabriel-Constantin
Abstract: The paper presents an application for virtual didactic laboratory dedicated for instrumentation classes using blockchain technology for saving students measurements data in order to ensure their uniqueness. The application is developed in Labview and it does both, the lab simulation and the data saving using blockchain technology in a local private wallet. The laboratory part is dedicated to a multimeter verification using an adjustable voltage source. The adjustable voltage source is based on a Feussner compensator and on a Weston standard. The blockchain part is connecting to the teacher private wallet and saves the data as a blockchain transaction every time when the student press the button. The application is delivered to the student as an executable program, so he does not know where and how the data is sent. Further, the lab part of the present application can be modified to use remote controlled instruments, except the comparator that can be replaced with a modern adjustable voltage source. The paper presents at the beginning the used blockchain technology, how the transaction are performed, how the traceability can be verified, how the data is organized within a transaction. Further, the lab part of the application is described. Each simulated instrument respects the construction error limits provided in their datasheets, while each individual run of the instrument will generate a uniquely random value within this interval. In the end some demo acquired data and discussions are provided.